Disequilibrium as Determinant of Reinforcement and Punishment Effects: A Replication. - Jacobs, Kenneth W.; King, James E.; Dowdy, Art (Psychological Record, 2024)
Response disequilibrium theory, an extension of the response deprivation hypothesis, proposes that behavior-change is due to disruptions in an organism's baseline levels of responding. This theory challenges the notion of distinct stimuli as reinforcers or punishers and instead emphasizes the role of instrumental and contingent activities. The present study aimed to test the predictions of response disequilibrium theory by replicating Heth and Warren's, Animal Learning & Behavior, 6, 294–300, (1978) experiment using a modernized apparatus. Sixteen undergraduate psychology students participated in the experiment, which included a familiarization period, baseline periods, and a contingency period. During the contingency period, the instrumental activity was the activation of a video that resulted in a deficit or excess of audio relative to baseline. According to response disequilibrium theory, a deficit will produce a reinforcement effect whereas an excess will produce a punishment effect. The results supported the predictions of response disequilibrium theory, as instrumental video activity increased for participants in the deficit condition and decreased for participants in the excess condition. In addition, the study revealed a strong correlation between the size of disequilibrium and the magnitude of behavior change. These findings further support the use of disequilibrium models to a priori identify effective contingency arrangements in both research and practice. Informal applications of the Premack principle may be supplanted with the precision of a formal model of reinforcement and punishment in response disequilibrium theory.